2015
DOI: 10.1097/pai.0000000000000071
|View full text |Cite
|
Sign up to set email alerts
|

BRAF and NRAS Mutations are Heterogeneous and Not Mutually Exclusive in Nodular Melanoma

Abstract: Inhibitors of RAF inhibit the MAPK pathway that plays an important role in the development and progression of those melanoma carrying the V600E BRAF mutation, but there’s a subset of such patients who do not respond to the therapy. Various mechanisms of drug resistance have been proposed which include the clonal heterogeneity of the tumor. We have studied a population of nodular melanoma to investigate the intratumor and intertumor heterogeneity by Laser Capture Microdissection (LCM) analysis. Our results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 29 publications
5
42
0
7
Order By: Relevance
“…This evidence has already been reported [16]. As previously observed [15,[17][18][19], in some samples we have detected co-occurrence of BRAF and NRAS mutations. At the single cell level, mutations in BRAF or NRAS are mutually exclusive [17].…”
Section: Discussionsupporting
confidence: 74%
“…This evidence has already been reported [16]. As previously observed [15,[17][18][19], in some samples we have detected co-occurrence of BRAF and NRAS mutations. At the single cell level, mutations in BRAF or NRAS are mutually exclusive [17].…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, intratumoural heterogeneous staining of NRASQ61R IHC is common in melanomas. 5,7,8,19,20 Intratumoural heterogeneity resulted from subclonal evolution within the tumour 8,[19][20][21] and existed between primary and metastatic melanomas. 5,7,22 Heterogeneous expression for NRASQ61R IHC was not observed in this study or in the study of follicular carcinomas conducted by Oishi et al 16 Diffuse and homogeneous expression for NRASQ61R IHC supports the concept that the RAS mutation is generally an early molecular aberration in the adenomacarcinoma pathway of CRCs.…”
Section: Discussionmentioning
confidence: 99%
“…Yancovitz et al reported the presence of distinct clonal populations with BRAF wild type or NRAS mutant cells together with cells containing BRAF V600E mutation within the same primary melanoma lesions (Yancovitz et al, 2012). Chiappetta et al described that NRAS and BRAF mutations in melanoma are not mutually exclusive as previously understood but instead co-occur at varying detectible frequencies within the same lesion (Chiappetta et al, 2014) (Sensi et al, 2006;Wilmott et al, 2012;Chiappetta et al, 2014). As highly selective therapies such as vemurafenib deplete the bulk of the tumors, the subpopulations of resistant cells survive, get enriched and promote tumor regrowth.…”
Section: Resistance To Braf Inhibitorsmentioning
confidence: 95%